Conceptual Change Texts to Improve Teachers’ Misconception at Verbal and Visual Representation on Heat Conduction Concept - Anam, R. S.; Widodo, A.; Sopandi, W. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
Heat Conduction is a scientific concept that related to daily life. Learning about heat conduction is usually only discussed at the macroscopic level, whereas at the sub-microscopic level never be a concern from elementary students until to the teachers. This study aims to identify the effect of using Conceptual Change Text on the teacher's representation on the Â heat conduction concept. A quasi-experimental method using a one-group pretest-posttest design was used in this study. The instrument was a diagnostic test, the data were analyzed from the comparison of participants' representations (5 elementary teachers) before and after treatment, the results showed that teacher representation was better after treatment. This research also reinforces that the representation of the sub-microscopic level is an important aspect of the learning process. Science learning needs to be developed and equipped up to the sub-microscopic level both verbal or visual to make science lessons more meaningful and easily understood by students.